Analisis Sistem Informasi Akuntansi Penerimaan Kas dan Billing System pada PDAM Tirta Lamaindo Kabupaten Buton Selatan - Misran, Misran (Yayasan Literasi Sains Indonesia, 2023)
This study aims to analyze the cash receipts accounting information system and the billing system at the Tirta Lamaindo Water Supply Company, South Buton Regency. This research was conducted from August to October 2023. Data collection methods used observation, documentation, and interviews. The data analysis method used is descriptive qualitative method. The results of the study show that the Cash Receipts Accounting Information System and Billing System can be said to be sufficient but not fulfilled in all components. This is due to the fact that there is one component of the accounting information system for the Tirta Lamaindo Water Supply Regional Public Company, South Buton Regency, which is not optimal according to the criteria, namely Employee Services. If there is one component that is not optimal, the accounting information system is not fully adequate. The data component has not fulfilled the objectives of the accounting information system for the Tirta Lamaindo Regional Public Company, South Buton Regency, as well as the use of a semi-conventional device, namely Microsoft Excel. In addition, the accounting information system has been able to fulfill the objectives of the accounting information system in providing information for decision making and for the implementation of the Company's operational activities.